Numerical investigation of the cross flow fluidelastic forces of two-phase flow in tube bundle - Sadek, Omar; Mohany, Atef; Hassan, Marwan (Journal of fluids and structures, 2018)
This paper presents a numerical model to predict the unsteady fluid forces in a parallel triangular array subjected to two-phase flow. The numerical model utilizes the RANS formulation with aid of Spalart–Allmaras turbulence model, while the physics of the two-phase flow are modeled by the mixture model, drift-flux model, and the interfacial area concentration concept. This numerical model was utilized to simulate an air–water flow in tube array with various air void fractions. The predicted fluid force coefficients were compared with the available experimental data. The comparison showed a good agreement in terms of the force magnitude and phase at various reduced flow velocities. The obtained force coefficients were employed in a Hybrid analytical-CFD model representing a kernel of 7 tubes. The stability was investigated by studying the eigen values of the system as a function of the flow velocity. In addition, the stability thresholds were examined by simulating the same 7 flexible tubes kernel in cross flow using the direct flow/structure coupling. The predicted stability threshold obtained via these two models agrees very well with the experimental counterparts. They represent a lower bound for the stability data. These results are very promising and represent an important step towards an analytical frame work to accurately predict the stability of tube arrays.